Global burden of lip and oral cavity cancer attributable to high alcohol consumption from 1990 to 2021 - Pang, Shimeng; Duan, Wei; Chen, Wei; Lu, Le (Frontiers in Nutrition, 2025)
BackgroundBased on data from the Global Burden of Disease (GBD) 2021, this study analyzes the global disease burden of lip and oral cavity cancer attributable to high alcohol consumption (LOC-HAC).MethodsDisability-adjusted life years (DALYs) were used to assess health loss. The Das Gupta decomposition method was employed to analyze the effects of population growth, aging, and epidemiological changes on DALYs. The Nordpred model was applied to project the disease burden trends from 2022 to 2045.ResultsIn 2021, the global number of DALY cases for LOC-HAC was 1,191,084 (95% UI: 906,229.2–1,474,007), representing a 90% increase from 628,484.1 (95% UI: 493,522.1–754,895.3) in 1990. The fastest growth occurred in low-middle SDI regions, reaching 279%. A similar increasing trend was observed in deaths, with Southeast Asia showing the most significant rise, where DALYs and deaths increased by 326 and 357%, respectively. The global age-standardized DALY rate (ASDR) of LOC-HAC in 2021 was 13.66 (95% UI: 10.4–16.9) per 100,000 population, with Central Europe having the highest ASDR and Southeast Asia experiencing the fastest growth. DALYs and deaths were significantly higher in males than in females and increased with age, peaking at 55–59 years in males and 60–64 years in females. SDI levels were positively correlated with ASDR and age-standardized mortality rates (ASMR). However, when the SDI exceeded 0.75, ASDR and ASMR showed a declining trend. Over the past 32 years, the global increase in DALYs and deaths has been primarily driven by population aging and growth. Projections indicate that from 2022 to 2045, DALYs and deaths among males will rise significantly, whereas the increase among females will be more gradual.ConclusionThe global burden of LOC-HAC has risen significantly over the past decades, especially in low-middle SDI regions and Southeast Asia. In the future, efforts should focus on these regions by promoting healthier lifestyles, strengthening early screening, and optimizing healthcare resource allocation to reduce disease burden.